Technology Roadmapping para startups : um método para a elaboração de Estratégias de Negócio - Garcia, Alexandre de Souza (Universidade do Vale do Rio dos Sinos, 2019)
The competitiveness of firms depends on the elaboration of effective strategies, making technological development as a central element. The researched scenario presents the technology-based startups as potentially disruptive actors. On the other hand, large firms use Technology Roadmapping (TRM) in order to position themselves competitively in the market, there is a theoretical and empirical gap as to ‘how’ startups can shape their business strategies from technology. Thus, this study deals with the incorporation of the technological factor in the startups business strategy. The analysis of TRM literature in this study is connected to the logic of Resource Based View (VBR). What is effected is an opening of the 'black box', something seen in Neoclassical literature as uninteresting, but defended by Neo Schumpeterian vision as important, viable and critical. The research methodology adopted in the study is Design Science Research, and the artifact proposed from the theoretical reference - MI1 (Intervention Method 1) was stenciled through the empirical sequential application in three technology - based startups, generating procedurally the MI2 Methods and MI3. Therefore, it is suggested a TRM method for startups, which aims to help this type of firm generate business strategies based on technology. Thus, the contributions can be divided into three topics: i) VBR: the logic of resources as essential factors for the firm's performance is considered with the inclusion of the variable 'Resources' in the proposed method and thus the VBR is proposed as theoretical barrier for the TRM in startups; ii) TRM: the method is developed for an object not yet addressed by the researchers of the area - the technology-based startups; iii) Industrial Economics: in this study there is an example of the opening of the 'black box', where the technology is used as input for new firm strategies, thus corroborating Neo Schumpeterian vision. Thus, the study may generate interest for new research focused on this object and, consequently, generate new applications, new concepts and new methods related to VBR, TRM and Industrial Economy.
Keywords: Technology Roadmapping; Estratégia; Startups; Visão baseada em recursos; Technology Roadmapping; Strategy; Startups; Resource based view; ACCNPQ::Ciências Sociais Aplicadas::Administração